2023
DOI: 10.2196/40716
|View full text |Cite
|
Sign up to set email alerts
|

Observed Interactions, Challenges, and Opportunities in Student-Led, Web-Based Near-Peer Teaching for Medical Students: Interview Study Among Peer Learners and Peer Teachers

Abstract: Background Near-peer teaching (NPT) is becoming an increasingly popular pedagogical tool in health professions education. Despite the shift in formal medical education from face-to-face teaching toward encompassing web-based learning activities, NPT has not experienced a similar transition. Apart from the few reports on NPT programs hastily converted to web-based learning in light of the COVID-19 pandemic, no studies to date have explored web-based learning in the specific context of NPT. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Although numerous studies identified 2-way communication, such as "learner-learner" [39,40] and "learner-instructor" interactions [39,[41][42][43], as the most important contributors to satisfaction with web-based learning, learner-learner interaction had a weak relationship with satisfaction in this study. A possible explanation for this finding may lie in the specific course objectives and instructional goal orientation.…”
Section: Principal Findingsmentioning
confidence: 72%
“…Although numerous studies identified 2-way communication, such as "learner-learner" [39,40] and "learner-instructor" interactions [39,[41][42][43], as the most important contributors to satisfaction with web-based learning, learner-learner interaction had a weak relationship with satisfaction in this study. A possible explanation for this finding may lie in the specific course objectives and instructional goal orientation.…”
Section: Principal Findingsmentioning
confidence: 72%